MALNUTRITION AMONG VAGRANT CHILDREN IN INDIA: A CRIMINO-GENIC PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
Malnutrition and vagrancy are two interconnected issues that affect a significant number of children in India. Children living on the streets or in vulnerable environments are often exposed to poor nutritional intake, limited access to healthcare, and a lack of social protection, all of which contribute to their malnourished state. This study explores the relationship between child malnutrition and vagrancy, focusing on the socio-economic factors contributing to both issues. Using a mixed-methods approach, the research examines the extent of malnutrition among vagrant children and investigates the survival strategies they employ in the absence of stable homes. The findings reveal that many of these children suffer from stunting, wasting, and underweight conditions, and face barriers in accessing government welfare programs. In-depth interviews and focus groups provide valuable insights into these children's coping mechanisms and the daily challenges they face. The study emphasizes the need for stronger, more accessible interventions and community-based solutions to address these pressing issues. Recommendations include the expansion of government welfare programs, improving access to education, and promoting family reintegration efforts.